Pengaruh rotasi auditor, audit fee, auditTenure, client importance, dan auditorSpesialisasi industri terhadap kualitas audit(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar diBursa Efek IndonesiaPeriode 2011-2014) - Dianti, Sekar Ayu; , Dra. Rina Trisnawati, Ak., M.Si (2016)
The objective of this study is to test the effect of auditor rotation, audit fee, audit tenure, client importance, and industrial auditor. Based on the literature review, it is suspected that the auditor rotation, audit fee, audit tenure, client importance, and industrial auditor variables have influences on auditor's quality. Data being used in this study are audited annual reports of various manufacturing companies registered at Indonesian Stock Exchange during 2011 to 2014. From the statistics test carried out using logistic regression, it is proved that: auditor rotation, audit fee, client importance, and industrial auditor have significant influence on the quality of audit meanwhile audit tenure does not have so. Probably it is caused by the longer the time required to do the audit, the less the independency of the auditor thus degrading the quality of the audit. For the future study of the effect of audit tenure, it is recommended to extend the duration of the observation according to the government policy, use another proxy, such as discretionary accrual, to measure the quality of the audit, and add other variables which might influence the quality of audit, such as auditor's reputation.